Colaboração e ressignificação de práticas de ensino e aprendizagem de inglês na escola pública: aventuras e desventuras em uma 3ª série do ensino médio - Silva, Eliseu Alves da (2018)
Studies on teaching and learning English as Additional Language (EAL) in State school (COELHO, 2005; PAIVA, 2007; TICKS, 2008; SCHERER; MOTTA-ROTH, 2015; CUNHA; STURM, 2015; PIMENTA; MOREIRA; REEDIJK, 2016) show that challenges of this task pass through questions of methodology, students’ (lack of) interest, teachers’ devaluation and low pay, insufficient workload in the discipline and so on. From this perspective, proposals of collaborative intervention in school contexts (TICKS, 2008; PASSONI, 2012; TICKS; SILVA; BRUM, 2013; SILVA, 2014) have focused on creating reflexive spaces aiming at ressignifying practices and promote emancipatory and collaborative learning. Thus, in this investigation we try to analyze the reflexive and collaborative process, developed within an English learning proposal as a socially situated activity in the State school in order to ressignify the participants’ (teacher and students) discourses and practices about English teaching and learning in this context. To do that, we initially investigated students’ representations about teaching and learning and roles of teacher and student in these processes. Then we started the implementation of the socially situated EAL learning proposal that involved practices of reading to subsidize a written production and, at the end, the production of an exemplar of the genre oral presentation in English. The learning proposal development tried to offer spaces to reflect and ressignify representations of teaching and learning and the roles of teacher and the student. The pedagogical proposal, the analysis and the reflection of the discourses produced along the process were theoretically supported by Collaborative Research (MAGALHÃES, 2002), Critical Discourse Analysis (FAIRCLOUGH, 1992; 2003), Argumentation (LEITÃO, 2009; 2011), Critical Genre Analysis (MEURER, 2002; MOTTA-ROTH, 2008b) and social theory of learning (VYGOTSKY, 1934/2001). The analysis of the initial representations of the students evidenced an English learning paradigm associated to traditional pedagogic perspectives of repetition and grammar memorization (COPE; KALANTZIS, 2015), helping to emerge teachers’ representations as learning provider/facilitator and student as receptor/beneficiary of the knowledge transmitted by the teacher, which were maintained during the process. Near the end, however, we perceived timid upholds on students’ discourses towards an awareness that English learning can happen beyond grammar memorization and that the acquired learning can be valid to other situations external to classroom. Nevertheless, these representations are still fragile because they were built within a non-continuous process, marked by many interruptions (downtimes and strikes). In the same way, these representations keep discursive echoes from Elementary school, based on repetition that could also be identified in the teachers’ practice, evidencing weaknesses and uncertainties inherent to the task of teaching in that context and giving the precise extent that to make a difference in the State school (practice) means to go through these difficulties.